Vasopressin and water distribution in rats with DOCA-salt hypertension - Kunes, J; Nedvídek, J; Zicha, J (Journal of hypertension. Supplement, 1989)
The role of vasopressin in the regulation of body water volume and its distribution to intravascular, interstitial and intracellular compartments, and the importance of particular body water compartments in the pathogenesis of DOCA-salt hypertension were studied in young Brattleboro rats. Vasopressin-deficient, vasopressin-synthesizing and vasopressin-deficient rats chronically supplemented with deamino-8-D-arginine vasopressin (dDAVP) were compared with water-drinking controls. The chronic DOCA-salt treatment caused a marked hypertension in vasopressin-synthesizing animals; in these animals body water was slightly increased due to the expansion of extra-cellular fluid volume whereas intracellular water tended to decrease, so that the ratio of extracellular fluid volume to intracellular water rose significantly. The development of DOCA-salt hypertension was attenuated in the vasopressin-deficient rats, which had a similar level of total body water, slightly increased intracellular water and significantly decreased extracellular fluid volume compared with the hypertensive vasopressin-synthesizing rats. Consequently, in the vasopressin-deficient rats, the ratio of extracellular fluid volume to intracellular water did not differ from that of controls. A vasopressin deficiency was associated with a failure to expand the interstitial fluid volume although plasma volume was increased. Unaltered total body water together with elevated plasma osmolality indicated an extracellular water deficiency in DOCA-salt-treated vasopressin-deficient rats. Chronic dDAVP supplementation restored the body fluid pattern and the hypertensive response of the DOCA-salt-treated vasopressin-deficient rats. In conclusion, the antidiuretic effects of vasopressin are necessary for the interstitial fluid volume expansion that is essential for a full development of DOCA-salt hypertension.
Keywords: Deamino Arginine Vasopressin; heterozygot; hypertenze; homozygot; Heterozygote; vasopresiny; deoxykortikosteron; Sodium Chloride; chronická nemoc; Vasopressins; Homozygote; Hypertension; Chronic Disease; Rats, Brattleboro; chlorid sodný; nefrektomie; krysa rodu Rattus; Animals; Body Water; zvířata; Rats; tělesná voda; Nephrectomy; Desoxycorticosterone; desmopresin; potkani Brattleboro